2022
DOI: 10.1364/oe.454023
|View full text |Cite
|
Sign up to set email alerts
|

Label-free imaging of intracellular organelle dynamics using flat-fielding quantitative phase contrast microscopy (FF-QPCM)

Abstract: Panoramic and long-term observation of nanosized organelle dynamics and interactions with high spatiotemporal resolution still hold great challenge for current imaging platforms. In this study, we propose a live-organelle imaging platform, where a flat-fielding quantitative phase contrast microscope (FF-QPCM) visualizes all the membrane-bound subcellular organelles, and an intermittent fluorescence channel assists in specific organelle identification. FF-QPCM features a high spatiotemporal resolution of 245 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 86 publications
2
10
0
Order By: Relevance
“…The results showed that the nucleus, nucleolus, and mitochondria, but not the entire endoplasmic reticulum or Golgi apparatus, were clearly visualized by ExAPC microscopy, similar to conventional label-free techniques (Fig. 1c) 10,15 .…”
Section: Visualization Of Cellular Organization In Living Cells At Hi...supporting
confidence: 56%
“…The results showed that the nucleus, nucleolus, and mitochondria, but not the entire endoplasmic reticulum or Golgi apparatus, were clearly visualized by ExAPC microscopy, similar to conventional label-free techniques (Fig. 1c) 10,15 .…”
Section: Visualization Of Cellular Organization In Living Cells At Hi...supporting
confidence: 56%
“…This is most likely due to the small RI contrast of these organelles. Interestingly, the ER network has been visualized by other QPI method . Visualization of these weakly scattering organelles calls for a higher imaging sensitivity and other analytical strategies.…”
Section: Recent Advances In Live Cell Imaging By Interference Microscopymentioning
confidence: 99%
“…The microscope technology based on interference imaging of complex linear scattered fields has made tremendous progress in the past two decades. Several schemes have been demonstrated for phase-sensitive imaging and detection, including but not limited to the interferometric scattering microscopy (iSCAT), coherent brightfield microscopy (COBRI), spatial light interference microscopy (SLIM), interferometric reflectance imaging sensor (IRIS), rotating coherent scattering microscopy (ROCS), , digital holographic microscopy (DHM), diffraction phase microscopy (DPM), , optical diffraction tomography (ODT, also known as tomographic phase microscopy), Fourier ptychographic microscopy (FPM), , partial-wave spectroscopic microscopy (PWS), , and quantitative DIC microscopy . These various techniques share a common working principle, that is to detect the complex signal fields through interference.…”
mentioning
confidence: 99%
“…Moreover, multilabel fluorescence staining is typically required, which increases the requirement of sample preparation and the microscope system’s complexity. Alternatively, label-free methods such as quantitative phase imaging hold great advantages where long-term observation of various organelles in an unlabeled cell is possible. …”
Section: Introductionmentioning
confidence: 99%